A comparative research investigation on different dominions of aggressiveness among professional Indian para throwers - Singh, V.; Krishna, N. R.; Catalin, C. V.; Singh Rajpurohit, R.; Bisht, P.; Nath, M.; Das, R.; Bhutia, T. N.; Zulbahri; Mario, D. T. (Journal of Physical Education and Sport, 2023)
Introduction- In the past few decades, there has been a notable surge in the number of sport possibilities available to those with disabilities, including elevated training and competitive chances. Athletes with disabilities who are able-bodied have just recently started to garner attention, and research on the psychosocial elements of disabled sports involvement is very new. Even less is therefore known about the psychological traits of athletes with disabilities who compete at a high level, like the Paralympic Games. In general, athletic aggression is a result of athletes' failures during competition, which encourages emotional changes in the form of irritation, impulsivity, trouble self-regulating, and other behaviours. There has been little research on the psychological factors supporting elite Indian paralympic athletes, particularly para throwers. Due to the lack of research on parasports, the primary research topic of this paper exclusively selects sports with Para athletes.